2016
DOI: 10.1371/journal.pone.0163158
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Mitochondrial Respiratory Dysfunction and Tissue Damage in Chronic Hyperglycemia Correlate with Reduced Aldehyde Dehydrogenase-2 Activity

Abstract: Aldehyde dehydrogenase (ALDH) 2 is a mitochondrial isozyme of the heart involved in the metabolism of toxic aldehydes produced from oxidative stress. We hypothesized that hyperglycemia-mediated decrease in ALDH2 activity may impair mitochondrial respiration and ultimately result in cardiac damage. A single dose (65 mg/kg; i.p.) streptozotocin injection to rats resulted in hyperglycemia with blood glucose levels of 443 ± 9 mg/dl versus 121 ± 7 mg/dl in control animals, p<0.0001, N = 7–11. After 6 months of diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 42 publications
(62 reference statements)
4
33
0
Order By: Relevance
“…To compare the Cyt c content in mitochondrial and cytosolic fractions, mitochondria were isolated from the ventricles as previously described. 65 At the end of perfusion, ventricle samples of Sham, I/R and PSELT 5 nmol/L groups were harvested and homogenized in mitochondrial isolation buffer ([IBc]: 0.1 mol/L Tris-MOPS, 0.1 mol/L EGTA-Tris and 1 mol/L sucrose, pH 7.4). Homogenates were centrifuged at 2000 9 g for 10 minutes at 4°C, and the supernatants were collected and centrifuged again at 5000 9 g for 10 minutes at 4°C.…”
Section: Mitochondrial Isolationmentioning
confidence: 99%
“…To compare the Cyt c content in mitochondrial and cytosolic fractions, mitochondria were isolated from the ventricles as previously described. 65 At the end of perfusion, ventricle samples of Sham, I/R and PSELT 5 nmol/L groups were harvested and homogenized in mitochondrial isolation buffer ([IBc]: 0.1 mol/L Tris-MOPS, 0.1 mol/L EGTA-Tris and 1 mol/L sucrose, pH 7.4). Homogenates were centrifuged at 2000 9 g for 10 minutes at 4°C, and the supernatants were collected and centrifuged again at 5000 9 g for 10 minutes at 4°C.…”
Section: Mitochondrial Isolationmentioning
confidence: 99%
“…In the cytoplasm, alcohol dehydrogenase converts ethanol into acetaldehyde which is metabolized in the mitochondria by aldehyde dehydrogenase [37]. Acetaldehyde accumulation and activation of aldehyde dehydrogenase 2, a mitochondrial isozyme of aldehyde dehydrogenase, have been shown to diminish mitochondrial respiration [38]. Our data demonstrated that acetaldehyde reduces respirasome levels in mitochondria incubated in respiration buffer ( Figure 5D,E), suggesting that active ETC is necessary for acetaldehyde to disrupt the respirasome.…”
Section: Discussionmentioning
confidence: 55%
“…20 In type-1 and type-2 diabetic models, we found increased 4-hydroxy-2-nonenal (4HNE) protein adducts in diabetic tissue. 21,22 Previous studies support aberrant posttranslational modification of OGG-1 contributes to decreased OGG-1 activity: in type 1 diabetic mice, O-GlcNAcylation of OGG-1 was increased corresponding to decreased OGG-1 activity. 23 Therefore, taken altogether, we hypothesize that 4HNE decreases OGG-1 activity by forming adducts with OGG-1 on critical sites in diabetic tissue.…”
Section: Introductionmentioning
confidence: 87%
“…The Western blot analysis was performed as described earlier. 22,25 In brief, protein samples from heart tissue PAN ET AL.…”
Section: Western Immunoblottingmentioning
confidence: 99%